Prescribing of Opioids and Benzodiazepines Among Patients With History of Overdose. Issue 5 (September 2019) - Griggs, Christopher; Wyatt, Stephen; Wally, Meghan K.; Runyon, Michael; Hsu, Joseph R.; Seymour, Rachel B.; Beuhler, Michael; Bosse, Michael J.; Fogg, Ryan; Gibbs, Michael; Haas, Eric; Jarrett, Steven; et al.
Abstract : Objectives: Addiction and overdose related to prescription drugs continues to be a leading cause of morbidity and mortality in the United States. We aimed to characterize the prescribing of opioids and benzodiazepines to patients who had previously presented with an opioid or benzodiazepine overdose. Methods: This was a retrospective chart review of patients who were prescribed an opioid or benzodiazepine in a 1-month time-period in 2015 (May) and had a previous presentation for opioid or benzodiazepine overdose at a large healthcare system. Results: We identified 60, 129 prescribing encounters for opioids and/or benzodiazepines, 543 of which involved a patient with a previous opioid or benzodiazepine overdose. There were 404 unique patients in this cohort, with 97 having more than 1 visit including a prescription opioid and/or benzodiazepine. A majority of prescriptions (54.1%) were to patients with an overdose within the 2 years of the documented prescribing encounter. Prescribing in the outpatient clinical setting represented half (49.9%) of encounters, whereas emergency department prescribing was responsible for nearly a third (31.5%). Conclusions: In conclusion, prescribing of opioids and benzodiazepines occurs across multiple locations in a large health care system to patients with a previous overdose. Risk factors, such as previous overdose should be highlighted through clinical decision support tools in the medical record to help prescribers identify patients at higher risk and to mobilize resources for this patient population. Prescribers need further education on factors that place their patients at risk for opioid use disorder and on alternative therapies to opioids and benzodiazepines.